Hypothyroidism and hyperthyroidism - Guerri, Giulia; Bressan, Simone; Sartori, Marianna; Costantini, Alisia; Benedetti, Sabrina; Agostini, Francesca; Tezzele, Silvia; Cecchin, Stefano; Scaramuzza, Andrea; Bertelli, Matteo (Acta Biomedica Atenei Parmensis, 2019)
Congenital hypothyroidism is a condition in which the thyroid gland does not produce enough thyroid hormones. It occurs in 1:2000-4000 newborns. Common clinical features include decreased activity and increased sleep, feeding difficulty, constipation, prolonged jaundice, myxedematous facies, large fontanels (especially posterior), macroglossia, distended abdomen with umbilical hernia, and hypotonia. Slow linear growth and developmental delay are usually apparent by 4-6 months of age. Without treatment, congenital hypothyroidism leads to severe intellectual deficit and short stature. Congenital hyperthyroidism occurs when the thyroid gland produces too much of the hormone thyroxine, which can accelerate body metabolism, causing unintentional weight loss and a rapid or irregular heartbeat. Hyperthyroidism is very rare and its prevalence is unknown. Common clinical features include unintentional weight loss, tachycardia, arrhythmia, palpitations, anxiety, tremor and sweating. Here we summarize the genes involved in congenital hypo- and hyperthyroidism and the tests we use for genetic analysis.